State of health of Leonid Brezhnev as an element of state apparatus (Journal of history, 2024)
The article analyzes the role of health status of Leonid Brezhnev, General Secretary of the Central Committee of Communist Party of the Soviet Union and the Chairmen of the Presidium of the Supreme Soviet of the USSR, as a major element of the state apparatus in the USSR. Using numerous sources, including notes and diaries of Brezhnev himself, notes of Brezhnev’s secretaries, memories of Brezhnev’s political companions, doctors and family members, the authors have reconstructed the dynamic changes in the health status of Brezhnev, and in which way these changes have impacted his work efficiency. Despite the fact that Brezhnev came to power already burdened by diseases and bad habits, his first decade as a leader of Soviet Union was very fruitful. This conclusion contradicts an established historiographical opinion that Brezhnev belonged to a type of a quite healthy, but lazy leader, who could not and did not like to perform the duties of the state and party leader, trying to evade them at every opportunity. The last seven years of Brezhnev’s rule are characterized by a sharp deterioration in health status that led to the alternating periods of decline and rise of Brezhnev’s work efficiency, which severely affected entire state apparatus. Despite the efforts of Brezhnev himself and the fact that Soviet bureaucracy managed to mostly compensate the periods of “stalling” and even the temporary unavailability of the leader, the USSR’s specific power mechanism started to malfunction during the second half of 1970s. Another consequence of Brezhnev’s decreased performance was the delegation of significant political power to the group of companions, led by Yuri Andropov and Konstantin Chernenko. Having occupied the post of head of state almost for life, being the leader of socio-political system, which actually did not have mechanism for a legal change of power, except for the death of a predecessor, sick and decrepit Brezhnev had to work hard and remain “a leader” until his death, including at the cost of drug addiction.Key words: L.I. Brezhnev, USSR, leader, health, illnesses, work efficiency, state apparatus, political power.